2019
DOI: 10.1523/jneurosci.1400-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

ApoE4 Alters ABCA1 Membrane Trafficking in Astrocytes

Abstract: The APOE 4 allele is the strongest genetic risk factor for late-onset Alzheimer's disease (AD). ApoE protein aggregation plays a central role in AD pathology, including the accumulation of ␤-amyloid (A␤). Lipid-poor ApoE4 protein is prone to aggregate and lipidating ApoE4 protects it from aggregation. The mechanisms regulating ApoE4 aggregation in vivo are surprisingly not known. ApoE lipidation is controlled by the activity of the ATP binding cassette A1 (ABCA1). ABCA1 recycling and degradation is regulated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
110
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 104 publications
(119 citation statements)
references
References 41 publications
(61 reference statements)
3
110
0
Order By: Relevance
“…At the low pH of endosomes, apoE4 is more favored than apoE3 to form a molten globule with its increased binding affinity to lipids (Morrow et al, 2002). ApoE aggregation has a role in neurodegenerative diseases such as AD (Rawat et al, 2019), predisposing the aggregation of interacting proteins, e.g., seeding of Aβ fibrils.…”
Section: Apoe Structure and Functionmentioning
confidence: 99%
“…At the low pH of endosomes, apoE4 is more favored than apoE3 to form a molten globule with its increased binding affinity to lipids (Morrow et al, 2002). ApoE aggregation has a role in neurodegenerative diseases such as AD (Rawat et al, 2019), predisposing the aggregation of interacting proteins, e.g., seeding of Aβ fibrils.…”
Section: Apoe Structure and Functionmentioning
confidence: 99%
“…It has further been shown that CS-6253 improved APOE lipidation, reduced amyloid and tau pathology, and mitigated APOE4-driven cognitive impairment in mice [163]. In a recent study, Rawat et al [209] reported that treatment with CS-6253 stabilizes membrane ABCA1 and promotes ABCA1 recycling in primary APOE4 astrocytes. These effects led to increased lipidation and decreased aggregation of APOE4.…”
Section: Apoe Mimetic Peptidesmentioning
confidence: 96%
“…A recent study comparing ApoE3 with E4 showed that ApoE4 had a greater ABCA1 binding affinity in CNS astrocytes (ApoE2 was not studied) (85). Genetic variants in ABCA1 are also implicated in AMD (8), and mouse models with RPE-specific deletion of ABCA1 show RPE atrophy and retinal degeneration (12).…”
Section: Accumulation Of Lipid Droplets Autophagic Defects and Mitocmentioning
confidence: 99%